Comparative Analysis of Weak Soils: Evaluating Geosynthetic Applications for Enhanced Stability and Load-Bearing Capacity - Шахмов, Жанболат (Вестник ВКТУ им. Д. Серикбаева, 2025)
Weak soil conditions present significant challenges in various civil engineering projects, including construction, slope stability, and infrastructure development. Weak soils are found in several regions, many loess and silty soils are most widespread in the central and southern Kazakhstan regions. This study presents a comparative analysis of weak soils, focusing on solid loam and plastic sandy silt specimens collected from regions in central and southern Kazakhstan. The research evaluates the effectiveness of geosynthetic applications in enhancing the stability and load-bearing capacity of these soil types. Through comprehensive laboratory testing, including liquid and plastic limit tests, determination of swelling potential, the geotechnical properties of both soils are examined. Investigations are conducted to determine the impact of geosynthetics on soil reinforcement, deformation control, and load distribution. Through a detailed analysis of the literature and experimental studies of the geotechnical properties of weak soils, this research explores conventional and innovative techniques employed for soil improvement. This study offers practical guidelines for engineers and researchers to optimize soil strengthening strategies, ensuring durability and reliability in civil engineering applications.